2011
DOI: 10.1002/minf.201000176
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Non‐Canonical Interactions to the Stability of Sm/LSm Oligomeric Assemblies

Abstract: The distinguishing property of Sm/LSm protein assemblies is their high stability. In order to better understand the nature of Sm/LSm protein oligomers in this study we have analyzed the contribution of non-canonical interactions to the stability of assemblies. The predominant types of non-canonical interactions at Sm/LSm protein interfaces are CH⋅⋅⋅O, and CH⋅⋅⋅N interactions represented at interfaces. Our results show low percentages of XH-π and non-canonical interactions involving sulfur atoms, while the back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The networks of hydrogen bonds between subunits are important for protein stability, functionality, and structural integrity . There are 903 hydrogen bonds across the 118 phycocyanin protein interfaces of our dataset.…”
Section: Resultsmentioning
confidence: 99%
“…The networks of hydrogen bonds between subunits are important for protein stability, functionality, and structural integrity . There are 903 hydrogen bonds across the 118 phycocyanin protein interfaces of our dataset.…”
Section: Resultsmentioning
confidence: 99%
“…In general they are very stable and sometimes the presence of chaotropic agent is necessary for their disruption [14,17]. We have previously reported contribution of hydrogen bonds, salt bridges and non-canonical interactions to the stability of Sm oligomers [21,22]. In our work [23], we showed that the hot spots of Sm proteins are located within densely packed regions; these are highly conserved and have large energy contributions to the interface interactions.…”
Section: Introductionmentioning
confidence: 49%
“…In an effort to search for the factors that contribute to the affinity and specificity of protein-protein interactions, many previous studies were aimed at the analysis of the properties of protein-protein interfaces. This manuscript expands on our previous work on the non-canonical interactions of Sm/LSm proteins [21,22] by analyzing the same class of proteins with respect to ππ interactions. We have systematically analyzed the influence of π-π interactions to the stability of Sm/LSm proteins.…”
Section: Introductionmentioning
confidence: 81%